Evaluasi Model Pembelajaran Gallery Walk untuk Meningkatkan Dimensi Gotong Royong pada P5 dalam Kurikulum Merdeka - Sajida Salwa Sholikah; Yesica Ade Ariawan; Septiana Tri Nurcahyani; Agus Sumarno; Muhammad Sabandi (CV. ITTC INDONESIA, 2025)
The gallery walk learning model is one of the strategic steps in building student behavior that is in line with the essence of Pancasila, especially in the implementation of the mutual cooperation dimension in P5. The purpose of this study is to evaluate the application of the gallery walk learning model in increasing the mutual cooperation dimension in students through the P5 program in the Independent Curriculum at SMA Negeri 1 Kartasura. This study applies a case study design, which is an empirical investigation design to investigate phenomena that actually exist. The results of the study show that the application of the gallery walk learning model can significantly raise students' awareness of the importance of mutual cooperation values. This can be seen from the increasing active involvement of students in group activities, both in sharing tasks, discussing, and providing feedback to other groups. Thus, this study is expected to be a reference for the development of relevant learning in the future to strengthen the values ​​of Pancasila, especially the values ​​of mutual cooperation.